The functional characterisation of the C-type lectin : Clecsf8 - Graham, Lisa Maria (University of Cape Town, 2015)
Includes bibliographical references (leaves 147-157). === Clecsf8 is a poorly characterised member of the "Dectin-2 cluster" and was originally thought to be expressed exclusively by macrophages. In this study it was demonstrated that Clecsf8 is primarily expressed by peripheral blood neutrophils and monocytes.